Metabolic Syndrome, and Particularly the Hypertriglyceridemic-Waist Phenotype, Increases Breast Cancer Risk, and Adiponectin Is a Potential Mechanism: A Case–Control Study in Chinese Women - Xiang, Yujuan; Zhou, Wenzhong; Duan, Xuening; Fan, Zhimin; Wang, Shu; Liu, Shuchen; Liu, Liyuan; Wang, Fei; Yu, Lixiang; Zhou, Fei; Huang, Shuya; Li, Liang; et al. (Frontiers in Endocrinology, 2020)
Objective: To investigate the association between metabolic syndrome and breast cancer and to elucidate the potential mechanism underlying this association. Patients and Methods: Based on baseline data drawn from 21 hospitals in 11 provinces of China, we performed a case–control study among 1127 women (595 cases and 532 controls), divided into premenopausal and postmenopausal subgroups. Student’s t-test, Pearson’s χ2 test, and logistic regression analyses were performed to ascertain the association between breast cancer and metabolic syndrome, including all of its components. In addition, we attempted to clarify the potential role of adiponectin in this association. Results: Among the components of metabolic syndrome, abnormal waist circumference was the component that markedly increased breast cancer risk in premenopausal women (OR 1.447, 95% CI 1.043–2.006). Metabolic syndrome with clusters of special risk factors showed an association with breast cancer risk. Among all these components of metabolic syndrome, the hypertriglyceridemic-waist (HW) phenotype significantly increased breast cancer risk (OR 1.56, 95% CI 1.02–2.39), regardless of menopausal status, rendering it a strong predictor of breast cancer. Total adiponectin levels and high-molecular-weight adiponectin were reversely associated with metabolic syndrome. In addition, total adiponectin levels among breast cancer patients were much lower than among controls (6.67±3.05 vs. 8.01±4.18, p=0.014) only in the HW phenotype subgroup. Furthermore, the HW phenotype was associated with increased risk of estrogen receptor/progesterone receptor-positive (ER+/PR+) and -negative (ER-/PR-) breast cancer, with a 51% (OR=1.51, 95% CI:1.03–2.21) and 69% (OR=1.69, 95% CI: 1.05–2.72), respectively. However, there was no significant association between the HW phenotype and the ER+/PR- subtype. These results suggested that low adiponectin levels may be a mechanism that explains the association between the HW phenotype and breast cancer risk. Conclusion: Metabolic syndrome with special cluster factors is related to breast cancer risk; particularly, the HW phenotype can be regarded as a strong predictor of breast cancer. As an important factor involved in fat metabolism, adiponectin may strongly predict metabolic syndrome, especially the HW phenotype and breast cancer. Further research into this mechanism and epidemiological studies are needed. This study provides new evidence for the role of a healthy lifestyle in preventing breast cancer.